EU railway policy on international corridors for rail freight: Example of the Orient/East-Med Rail Freight Corridor No. 7 - Gerhard Troche (Spatial and transport infrastructure development in Europe: Example of the Orient/East-Med Corridor, 2019)
The Orient/East-Med Corridor, connecting central and southeastern Europe, provides important business potential for European rail freight. However, freight transport by rail faces a number of challenges in terms of quality, cost competitiveness, service features and political/societal acceptance and support. A particular challenge is the slow implementation of a truly Single European Rail Area, leading to high costs and time losses at borders. As a response to this, so-called EU Rail Freight Corridors (RFCs) have been set up, one of them being the Orient/East-Med RFC No. 7, established in November 2013 and aiming at better cross-border coordination and cooperation in the field of infrastructure and traffic management and improved customer orientation and involvement of corridor users. Key features of the Rail Freight Corridors are strong governance structures with clearly defined tasks. Among the early positive effects are the elaboration and testing of new solutions for cross-border processes, better coordination in timetable planning and the setting up of cross-border working groups, bringing relevant actors together to address specific issues. At the same time there is room for further improvement both conceptually and in terms of the corridor geography. The establishment of two further Rail Freight Corridors in the region, the Alpine-Western Balkan RFC No. 10 and the Amber RFC No. 11 closes some remaining gaps in the network of corridors. – – Im Orient/East-Med Corridor, der Mittel- und Südosteuropa verbindet, steckt ein wichtiges kommerzielles Potenzial für den europäischen Schienengüterverkehr. Der Schienengüterverkehr in Europa steht jedoch vor einer Reihe von Herausforderungen in Bezug auf Qualität, Kostenwettbewerbsfähigkeit, Leistungsmerkmale sowie politische/ gesellschaftliche Akzeptanz und Unterstützung. Eine besondere Herausforderung ist die nur schleppende Umsetzung eines wirklich einheitlichen europäischen Eisenbahnraums, was zu hohen Kosten und Zeitverlusten an den Grenzen führt. Als Reaktion hierauf wurden sogenannte EU Schienengüterverkehrskorridore (Rail Freight Corridors = RFCs) geschaffen, darunter der im November 2013 eingerichtete Orient/East-Med RFC Nr. 7, der auf eine bessere grenzüberschreitende Koordination und Zusammenarbeit im Bereich Infrastruktur und Verkehrsmanagement sowie eine verbesserte Kundenorientierung und Einbindung der Nutzer der Korridore abzielt. Hauptmerkmale der Schienengüterverkehrskorridore sind effektive Verwaltungsstrukturen mit klar definierten Aufgaben. Zu den bereits feststellbaren positiven Effekten gehören die Erarbeitung und Erprobung neuer Lösungen für grenzüberschreitende Prozesse, eine bessere Koordinierung der Fahrpläne und die Einrichtung von grenzüberschreitenden Arbeitsgruppen, die relevante Akteure an einen Tisch bringen, um spezifische Probleme anzugehen. Gleichzeitig gibt es sowohl konzeptionell als auch in Bezug auf die Geographie der Korridore Raum für weitere Verbesserungen. Die Einrichtung von zwei weiteren Schienengüterverkehrskorridoren in der Region, dem Alpine-Western Balkan RFC No. 10 und dem Amber RFC No. 11, schließt einige verbleibende Lücken im Korridornetz.
urn:nbn:de:0156-0952098; hdl:10419/213084; https://econpapers.repec.org/RePEc:zbw:arlfob:12
Keywords: 710; rail freight; european corridors; transport policy; TEN-T; infrastructure management; traffic management; Southeastern Europe; Schienengüterverkehr; europäische Korridore; Verkehrspolitik; TEN-V; Infrastrukturmanagement; Verkehrsmanagement; Südosteuropa